2020
DOI: 10.1002/marc.202000458
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Fiber Reinforced Epoxy Vitrimer: Robust Mechanical Performance and Facile Hydrothermal Decomposition in Pure Water

Abstract: Conventional carbon fiber reinforced thermosetting polymers (CFRPs) are neither recyclable nor repairable due to their crosslinked network. The rapid growing CFRP market raises a serious concern of the waste management. In this work, a viable method to develop a readily recyclable CFRP based on epoxy vitrimer is introduced. First, a self‐catalytic epoxy prepolymer with built‐in hydroxy and tertiary amine groups is designed, which upon reaction with an anhydride formed a catalyst‐free epoxy vitrimer. The epoxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 19 publications
(22 reference statements)
1
23
1
Order By: Relevance
“…In contrast to previous reports, we found that TOTGE–MDA vitrimers can undergo the DTER without the need for additional catalysts. This is because the reaction of TOTGE with MDA generates a large number of β-hydroxy esters and tertiary amines, which act as catalysts and allow the vitrimers to undergo the DTER and achieve the topological rearrangements previously reported. , …”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…In contrast to previous reports, we found that TOTGE–MDA vitrimers can undergo the DTER without the need for additional catalysts. This is because the reaction of TOTGE with MDA generates a large number of β-hydroxy esters and tertiary amines, which act as catalysts and allow the vitrimers to undergo the DTER and achieve the topological rearrangements previously reported. , …”
Section: Resultsmentioning
confidence: 84%
“…The catalysts of DTERs are toxic, poorly compatible, and sensitive to corrosion. Therefore, the development of catalyst-free vitrimers based on a DTER is of great importance. The introduction of tertiary amines into the vitrimer network is an effective solution. , Zhang’s group introduced triethanolamine as a co-curing agent into a DER331 epoxy resin and anhydride network. The vitrimer network underwent a rapid DTER and achieved self-healing catalyzed by tertiary amine in triethanolamine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past years, several vitrimer composites with diverse synthetic or natural monomers and dynamic formulations have been applied in continuous glass or carbon fiber reinforcements, showing promising mechanical properties compared to their thermoset counterparts [ 6 , 10 , 19 , 20 , 23 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Some vitrimer formulations have attractive properties such as a high tensile strength, interlaminar shear strength or glass transition temperatures [ 6 , 23 ].…”
Section: Introductionmentioning
confidence: 99%